Lucien Hervé: connecting eye the journey as a source for intercultural dialogue - Gebauer, Imola (Revelar: Revista de Estudos da Fotografia e Imagem, 2018)
Lucien Herve, Le Corbusier's photographer, found in his "world tour" and several "tours de France" a source of creation. In 1961, he parted on his biggest (six-month long) journey to fulfil photographic commissions for architects in the Mediterranean Basin, in Asia and in the Americas. This tour - with some other shorter ones - led him to discover and understand diverse cultures, their modernity and their con tribution to the technical and artistic development of the Western societies and became the principal source of his reflexions and exhibitions in the following decades. Paralyzed by multiple sclerosis from 1965 he wouldn't be able to undertake big trips anymore. His articles - most of them unknown today -, published in the first illustrated professional magazines of the 1950s reveal the photographer's immediate impressions as well as the results of his deep studies on the countries and cultures visited, inviting his public to follow him on an imaginary journey. His itinerant exhibitions composed by himself initiated a contemplative dialogue - a renewed, metaphorical journey - between these exotic places and the scenes of his "tours de France", that lasted more than 30 years. In his quest to reveal a universal human language he linked these distant and close 'terrae incognitae' and transfigured them. This article focuses on the tour-experience as a fundamental resource of the oeuvre of the photographer. It proposes the study of commissioned subjects as well as personal discoveries, of the shots on distant cultures beside those taken in France hoping to understand more this unique photographic language.